PREVALLENCE OF SCHISTOSOMIASIS (URINARY BILHARZIA) IN SINAZONGWE DISTRICT - Siankuku, Munsaka (Global Journal of Health Sciences, 2021)
Purpose of study: This study investigated the prevalence of Urinary Schistosomiasis in Zambia's Sinazongwe district. Methodology: Three primary schools in Sinazongwe district were sampled by convenient sampling and these were: Mwezya primary, Sinakasikili primary and Maamba private. 542 urine samples were collected from pupils examined in the laboratory at Maamba Hospital. Snail survey was carried out along 3 streams that are near the selected schools; Siamaambo stream which is near Mwezya primary school, Kanzinze stream which is near Sinakasikili primary school and another stream also called Kanzinze which is near Maamba private school. Findings: Study revealed that schistosomiasis is still highly existent in the district despite the ongoing administration of praziquantel; nonetheless, most of the infections are of low intensity and more males were infected than females. From the snail survey, Bulinus globosus the intermediate host for Schistosoma haematobium was found to be among the several snail species in Siamaambo stream and released cercaria when exposed to a light source, therefore they were infected and were/are the source of the bilharzia infection in Mwezya (Mwezya primary school). Unique contribution to theory, practice and policy: From results obtained, it can be seen that despite the administration of praziquantel to school going children, schistosomiasis will still be a problem in Sinazongwe district because the source of infection is not dealt with; as a result, there is continuous re-infection of the treated and untreated children. Therefore, comprehensive control by chemotherapy and snail control to eradicate the disease or at least lower the prevalence is recommended; and health officials that are involved in the administration of praziquantel should make follow-ups time-to-time after drug administration to evaluate the effectiveness of prophylactic program. Health education and provision of tap water is also recommended in this area to reduce frequent contact with contaminated water in streams.